Effects of erbium doping of indium tin oxide electrode in resistive random access memory. (18th February 2016) - Chen, Po-Hsun; Chang, Kuan-Chang; Chang, Ting-Chang; Tsai, Tsung-Ming; Pan, Chih-Hung; Lin, Chih-Yang; Jin, Fu-Yuan; Chen, Min-Chen; Huang, Hui-Chun; Lo, Ikai; Zheng, Jin-Cheng; Sze, Simon M.
Abstract: Identical insulators and bottom electrodes were fabricated and capped by an indium tin oxide (ITO) film, either undoped or doped with erbium (Er), as a top electrode. This distinctive top electrode dramatically altered the resistive random access memory (RRAM) characteristics, for example, lowering the operation current and enlarging the memory window. In addition, the RESET voltage increased, whereas the SET voltage remained almost the same. A conduction model of Er-doped ITO is proposed through current–voltage ( I – V ) measurement and current fitting to explain the resistance switching mechanism of Er-doped ITO RRAM and is confirmed by material analysis and reliability tests.